An Analysis of Business Model Canvas on a Comedy Company (A Study Case of Majelis Lucu Indonesia/PT. Jenaka Sumber Rezeki) - Ilham, Moh; Awaludin, Azrul Afrillana (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
This study aims to determine the business model of a talent development company or comedy company at Majelis Lucu Indonesia (MLI) / PT. Jenaka Sumber Rezeki, especially regarding the Business Model Canvas (BMC) analysis. The business model is one method that helps companies tell stories about a company's internal conditions. Through BMC, companies can display the nine essential components of a business in a simple but comprehensive way. The research data was obtained from the results of a literature study in the form of books, news articles, journals, YouTube video content, researchers’ experiences, and other supporting literature sources. The results obtained from this study were that the MLI company optimally implemented the nine components of BMC and benefited from various business sources such as talent management fees, YouTube Adsense, selling merchandise, holding special online and offline shows, MLI Music, MLI e-sports, and endorsements. Keyword: Business Model Canvas, Comedy Canvas, Majelis Lucu Indonesia